2018
DOI: 10.3390/ijms19061813
|View full text |Cite
|
Sign up to set email alerts
|

Lead (Pb) Exposure Enhances Expression of Factors Associated with Inflammation

Abstract: The human immune system is constantly exposed to xenobiotics and pathogens from the environment. Although the mechanisms underlying their influence have already been at least partially recognized, the effects of some factors, such as lead (Pb), still need to be clarified. The results of many studies indicate that Pb has a negative effect on the immune system, and in our review, we summarize the most recent evidence that Pb can promote inflammatory response. We also discuss possible molecular and biochemical me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
95
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(99 citation statements)
references
References 121 publications
(175 reference statements)
3
95
0
1
Order By: Relevance
“…Ranked the second most toxic substance on the priority list created by the Agency for Toxic Substances and Disease Registry (ATSDR) in 2017 [6], Pb poses a particular risk to the nervous system, especially in early life [7][8][9][10][11]. It is linked to numerous metabolic and structural changes in the developing brain (for detailed review see [12][13][14][15]), resulting in various cognitive disorders [16][17][18][19]. Children exposed to Pb in the early stages of development show a high incidence of many neurodevelopmental diseases, such as hyperactivity, emotional symptoms and conduct disorder [20], attention-deficit hyperactivity disorder (ADHD) [21,22], autism spectrum disorder (ASD) [23][24][25][26], and tend to have lower IQs [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Ranked the second most toxic substance on the priority list created by the Agency for Toxic Substances and Disease Registry (ATSDR) in 2017 [6], Pb poses a particular risk to the nervous system, especially in early life [7][8][9][10][11]. It is linked to numerous metabolic and structural changes in the developing brain (for detailed review see [12][13][14][15]), resulting in various cognitive disorders [16][17][18][19]. Children exposed to Pb in the early stages of development show a high incidence of many neurodevelopmental diseases, such as hyperactivity, emotional symptoms and conduct disorder [20], attention-deficit hyperactivity disorder (ADHD) [21,22], autism spectrum disorder (ASD) [23][24][25][26], and tend to have lower IQs [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Occupational and environmental exposure to metals and metalloids can cause many pathological conditions, including immunotoxicity. Research has shown that the most important mechanism underlying diseases associated with lead exposure is inflammation (1)(2)(3). Inflammation also plays a major role in the development of atherosclerosis (4,5).…”
mentioning
confidence: 99%
“…Numerous scientific studies have shown the link between lead exposure and cardiovascular abnormalities such as coronary artery disease, atherosclerosis, stroke, peripheral arterial disease, and arterial hypertension (11)(12)(13)(14). Many have also established that lead exposure is closely related to inflammation (2,15,16) and that it increases pro-inflammatory cytokine production, including tumour necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-10 (IL-10) (17,18).…”
mentioning
confidence: 99%
“…THP-1 macrophages were pretreated with the compounds at 10, 20 and 50 μM for 1 h, and then stimulated with LPS (1 μg/mL) for 24 h. As shown in Figure 4, LPS induced a significant increase in the production of TNF-α, IL-6 and IL-1β in THP-1 cells in relation to unstimulated control cells (p < 0.001). These molecules are potent pro-inflammatory cytokines produced by immune cells at the site of inflammation, and play a crucial role in local and systemic inflammatory responses [16]. Dexamethasone, used as an anti-inflammatory reference drug, strongly inhibited LPS-induced TNF-α, IL-6, and IL-1β production.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%